2016
DOI: 10.1111/jopr.12435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot Chemical Etching and 10‐Metacryloxydecyl Dihydrogen Phosphate (MDP) Monomer on the Bond Strength of Zirconia Ceramics to Resin‐Based Cements

Abstract: The use of the hot chemical etching method for 10 minutes increased the shear bond strength of zirconia ceramics to both conventional and resin cements and seems to be an effective method. The MDP monomer-containing resin cement, Panavia SA, improved the resin bonding of zirconia ceramics when combined with airborne-particle abrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
3
25
0
4
Order By: Relevance
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia . The results of the this study are in agreement.…”
Section: Discussionsupporting
confidence: 89%
“…,34 Some studies have shown that bypassing a surface treatment technique such as sandblasting or SIE results in low bond strength values, even when MDP-based luting agents are used 25,34. Many studies have reported that sandblasting combined with phosphate ester monomers containing agents provides good bond strength to zirconia 10,12,15,[20][21][22][23]25,31,35,36. The results of the this study are in agreement.…”
supporting
confidence: 84%
“…This larger bonding surface has more defects than smaller surfaces in a microtensile test. Therefore, the use of SBS test in this study could be thought of as a limitation . However, the results obtained for high‐strength ceramics with the 2 test methods were found to be similar .…”
Section: Discussionmentioning
confidence: 81%
“…This silica layer was not bonded or firmly attached to the zirconia surface, compromising durable adhesive joints. 12 Several surface treatments, such as laser irradiation 11,13 and hot chemical etching, 14 have been explored to increase resin to zirconia bond strength. Although air particle abrasion continues to be a simple and effective method with strengthening effect, a weakening effect on zirconia strength has been reported.…”
mentioning
confidence: 99%
“…In addition, in a very short time it is necessary to remove surface contamination, form roughness from the surface to provide mechanical clamping, and increase the number of areas for chemical bonding between the cement and the ceramic surface . Several applications have been proposed for connecting resin to zirconia surface, including hot chemical etching, rotary systems, gas‐phase fluorination, selective infiltration etching, nano‐alumina coating, tribochemical silica coating, airborne‐particle abrasion, hydrofluoric acid etching after fused glass‐ceramic application, and various laser irradiation …”
Section: Introductionmentioning
confidence: 99%